Ecology and distribution of Aulacoseira species (Bacillariophyta) in tropical reservoirs from Brazil - Bicudo, Denise C.; Tremarin, Priscila I.; Almeida, Pryscilla D.; Zorzal-Almeida, Stéfano; Wengrat, Simone; Faustino, Samantha B.; Costa, Lívia F.; Bartozek, Elaine C.R. [UNESP]; Rocha, Angélica C.R.; Bicudo, Carlos E.M.; Morales, Eduardo A. (Taylor & Francis, 2016)
Ecological preferences and distribution of Aulacoseira species in southeastern Brazilian reservoirs with varying trophic states were studied. One hundred and fourteen plankton samples (winter and summer) from 57 sites located in 16 reservoirs were analysed. Ten water quality parameters were measured. Ten Aulacoseira species were identified using light, scanning and transmission electron microscopy, and new information on their ecological preferences is provided here. Our results indicate that trophic gradient is the main driver of species distribution. Principal components analysis and calculation of weighted average nutrient optima revealed three indicator taxa, Aulacoseira tenella characteristic for oligotrophic waters and two varieties of Aulacoseira granulata (nominate and var. angustissima) typical for eutrophic reservoirs. This is the first ecological study of Aulacoseira in Brazil, adding information on the distribution of this genus in the tropics, and highlighting the need for species-level identification and regional studies to improve the use of diatoms in water quality assessment.
Keywords: autecology; bioindication; centric diatoms; South America; taxonomy; weighted average